How to Play Out of Equilibrium: Beating the Average - Karl Schlag (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We propose a new concept for how to make choices in games without assuming an equilibrium. To beat the average means to obtain a higher payoff against the others than the others obtain amongst themselves, for any way in which the game might be played. Only Nash equilibrium strategies can beat the average. Beating the average is possible in many symmetric games, including Cournot competition with convex demand. In many other games, including Betrand competition, there are strategies that “almost” beat the average. The methodology is easy to implement and extremely versatile, for instance it can incorporate incomplete information.
Keywords: 330